(+)- and (−)-actinoxocine, and actinaphthorans A–B, C-ring expansion and cleavage angucyclinones from a marine-derived Streptomyces sp. Issue 24 (31st October 2019) - Zhang, Shumin; Zhang, Lu; Fu, Xinzhen; Li, Zhi; Guo, Lin; Kou, Lijuan; Liu, Ming; Xie, Zeping
Abstract : A pair of enantiomeric C-ring expansion angucyclinones with an unprecedented epoxybenzo[ f ]naphtho[1, 8- bc ]oxocine carbon skeleton, and two unique C-ring cleavage analogues, were isolated from a marine-derived Streptomyces sp. Abstract : (+)- and (−)-actinoxocine (1 ), a pair of enantiomeric C-ring expansion angucyclinones, featuring a unique epoxybenzo[ f ]naphtho[1, 8- bc ]oxocine carbon skeleton, and two unusual C-ring cleavage analogues, actinaphthorans A–B (2–3 ), were isolated from a marine-derived Streptomyces sp. Their structures and absolute configurations were assigned by spectroscopic analysis, X-ray diffraction and CD calculations.